Differential effects of interleukin-2 and interleukin-4 on immunomodulatory role of platelet-activating factor in human B cells. - Patke, C L (1994)
Platelet-activating factor (PAF), a naturally occurring phospholipid cytokine, is a potent mediator of allergic and inflammatory reactions, as well as a modulator of immune responses. In the present study we showed that PAF is involved in early B-cell activation, as demonstrated by the increased cyclic AMP (cAMP) generation by PAF in a time- and dose-dependent manner in anti-mu antibody- plus B-cell growth factor-activated normal human peripheral blood B lymphocytes. PAF also regulated differentiation by causing a biphasic response on immunoglobulin M (IgM) production with an inhibitory signal generated at 10(-6) M and a stimulatory signal generated at 10(-8) to 10(-10) M. PAF enhanced IgA secretion. The regulation exerted by PAF was shown to be specific because the addition of the PAR antagonist CV-3988 abrogated these effects and the inactive form of PAF, lyso-PAF, induced neither cAMP generation nor immunoglobulin secretion in normal human B cells. Other cytokines, interleukin-2 (IL-2) and IL-4, potent mediators of the immune response, were unable to elicit a cAMP response in B cells. However, the addition of PAF (10(-6) M) with wither IL-2 or IL-4 enhanced cAMP production above the levels enhanced by the addition of PAF alone. IL-2 or IL-4, individually, stimulated IgM production, yet costimulation with PAF resulted in a differential effect between IL-2 and IL-4. PAF down-regulated the IL-4-induced IgM secretion, whereas the IL-2-induced IgM secretion was enhanced. The presence of CV-3988 returned all valued to those obtained with IL-2 or IL-4 alone, demonstrating the specificity of PAF. These data suggest that PAF is an important B-cell immunomodulator which can interact with other leukocyte cell mediators.